Pemanfaatan Teknologi Pendidikan dalam Dunia Pedidikan Islam untuk Menghadapi Era Society 5.0 - Mochammad Sirojul Munir (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2022)
Law number 20 of 2003 explains that National Education functions as capacity building and forms dignified national character and civilization in order to educate the nation's life, aims to develop the potential or ability of students to become human beings who believe and fear God Almighty, having noble character, being independent, healthy, knowledgeable, capable, creative, and being a democratic and responsible citizen. Nowadays every life can never be separated from the name of technology. Previously, there was an industrial revolution 4.0 initiated by Germany, now the world is again faced with the transition of the era of society towards the era of super-smart society, or better known as society 5.0, which was initiated by the Japanese people. in various fields in the industrial era 4.0 gave rise to human roles that were replaced by the presence of intelligent robots so that they could degrade human existence. In anticipation of this global trend, a transitional step is needed to the era of society 5.0, namely a concept of society that focuses on the development of aspects of human life (human-centered) based on technology (technology based), especially in the field of Islamic Religious Education. The integration of Islamic Religious Education in the use of technology in the era of society 5.0 is where when explaining about an Islamic religious education material it can be supported by assistance using technology without having to eliminate social interaction. Because, in this very modern world, students do not want to merely accept or absorb dogmatically every religious subject matter they receive. However, critically they will also question the religious education material that we convey in accordance with the reality in everyday life, because one of the functions of society 5.0 is to highlight social interaction.